Penggunaan Reward untuk Meningkatkan Pembiasaan Disiplin Anak di Taman Kanak-Kanak - Hesti Mayasari; Larasati Larasati; Najwa Lubis; Kholidah Nur (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
The current challenge is the absence of proper attitudes and behaviors in children when it comes to developing discipline in their activities. This issue is influenced by methods or developmental aspects that have not been fully optimized. Some children still struggle to show disciplined behavior, such as not queuing when using the toilet or fighting over toys with others. The goal of this article is to explore how rewards can improve children's discipline habituation. Using rewards as a strategy to foster discipline in children is an effective way to help them develop disciplined behavior. The research approach used in this study is a descriptive quantitative method with a literature review. The data collection involves analyzing primary sources, such as relevant books and journals, and then drawing connections between the issues and the applicable theories. The results from various sources suggest that reward-based strategies to improve children's discipline are highly effective and should be implemented. This method positively affects several developmental aspects, such as promoting responsibility, encouraging self-control, motivating children to improve their activities, and shaping their character for the future.